PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN TINDAK PIDANA PERSETUBUHAN: STUDI KASUS PENANGANAN DI POLRES PASURUAN - Zenita Delia Reviska; Maria Maria; Novita Apriyani (Universitas Labuhanbatu, 2026)
Child victims of sexual intercourse crimes face not only physical harm but also severe and long-term psychological consequences. This study aims to analyze the forms of legal protection provided to child victims and to identify the obstacles and handling mechanisms in law enforcement practices, with a case study at the Pasuruan Regional Police (Polres Pasuruan). This research employs an empirical juridical method with statutory, case, and conceptual approaches. Data were collected through interviews, observations, and literature review. The findings indicate that legal protection at Polres Pasuruan has been implemented through both repressive and preventive measures. Repressive measures include the protection of victims’ identities, detention of perpetrators, provision of psychological assistance, and placement of victims in safe houses. Preventive efforts involve public outreach and education programs. However, several practical challenges remain, including the limited availability of professional support personnel, underreporting due to cultural stigma, and suboptimal inter-agency coordination in the victim recovery process. These findings highlight that the effectiveness of legal protection depends not only on normative frameworks but also on institutional capacity and socio-cultural sensitivity in handling such cases. This study contributes by proposing an integrated institutional approach and a victim-oriented framework to strengthen the protection of child victims within the criminal justice system.Keywords: Child Protection; Sexual Offense; Legal Protection; Victim-Oriented Approach; Pasuruan Police